Grassroots Innovation: Minds on the Margin are not Marginal Minds - Gupta, Anil K; Aneet (Gyan Management Journal, 2016)
The editor talks about his life a bit and his motivation to work with innovators at the bottom of the pyramid. He talks about setting up the honeybee network that aims at documenting the innovations at grassroots, especially in remote villages. It aims to connect innovators so that they can benefit from each other’s work. It aims at helping them with technology and intellectual property knowhow. He talks about finding the National Innovation Foundation and SRISHTI, some of the organizations taking care of various aspects of innovations in the country.Journeys of his and his team are Shodhyatra - a bi-annual exploratory walks that they do in remote villages in India to discover the innovations happening there. They meet the villagers, they talk to the school kids and they invite the innovators to showcase their work to the world. Prof Gupta shares some of the Grassroots Innovations that they gathered on the way. He talks about how creative people in our villages are despite their limited resources and challenges in life. He shares examples that can be replicated. He specifically talks about women innovators and how their contribution goes unacknowledged. He points out that Grassroots Innovators don’t hang a board outside their home declaring their innovations. So, he goes out looking for them on these Shodhyatras.